Eco-tonality. An ecology with sound in capitalist ruins - Barbierato, Leonardo (Forum+, 2025)
Abstract When an ecosystem and an improvisational system overlap, an eco-tonality emerges: a transition zone that reveals latent characteristics of the two systems at play. This article explores the margin between improvised music performance and soundscape from a trans-disciplinary perspective, integrating ecology, post-human philosophy and improvisational practice. As a case study, my performance [in situ] will be examined to analyse eco-tonality through its key features. Abstract Wanneer een ecosysteem en een improvisatiesysteem elkaar overlappen, ontstaat er een ecotonaliteit (eco-tonality): een overgangszone die latente kenmerken onthult van de twee systemen. Dit artikel onderzoekt de grens tussen geïmproviseerde muziekperformance en soundscape vanuit een transdisciplinair perspectief, waarbij ecologie, posthumanistische filosofie en improvisatiepraktijk worden geïntegreerd. Als casestudy wordt mijn performance [in situ] onderzocht om ecotonaliteit te analyseren aan de hand van haar belangrijkste kenmerken.